Hubungan Antara Pola Asuh Orang Tua Yang Otoriter Dengan Kenakalan Remaja Pada Siswa Madrasah Aliyah Miftahul Ulum Kepuhkembeng Peterongan Jombang - Solichatun Solichatun (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2020)
This study aims to determine the relationship between authoritarian parenting and juvenile delinquency in students of Madrasah Aliyah Miftahul Ulum Kepuhkembeng Peterongan Jombang. This type of research is quantitative with a correlative approach. The population was all students of Madrasah Aliyah Miftahul Ulum Kepuhkembeng Peterongan Jombang, with a random sampling technique of 12.5% ​​of the population, namely 38 students. To obtain data about authoritarian parenting styles and juvenile delinquency data using a questionnaire. As for testing the hypothesis, the author uses statistical methods with the Product Moment correlation formula and the T test. Based on the calculation of the Product Moment correlation, the results obtained r XY (r count) = 0.879, which is greater than the value of the table criticism, a significant level of 5% (0.320), which means that there is a relationship between authoritarian parenting and juvenile delinquency in Madrasah Aliyah Miftahul Ulum Kepuhkembeng students. Peterongan Jombang. So that the proposed hypothesis can be accepted. Thus it can be said that the more parents apply authoritarian parenting, the greater the "reaction" shown by adolescents or in other words that authoritarian parenting will greatly support juvenile delinquency.